Digestive Enzyme Inhibition of Different Phenolic Fractions and Main Phenolic Compounds of Ultra-High-Pressure-Treated Palm Fruits: Interaction and Molecular Docking Analyses - Qingfeng Zhou; Jiexin Zhou; Xiaojing Liu; Yan-Bing Zhang; Shengbao Cai (Journal of Food Quality)
The purpose of the present work was to evaluate the inhibitory effects of different phenolic extracts from non- and ultra-high-pressure- (UHP-) treated palm fruits and their main phenolic compounds against pancreatic lipase and α-glucosidase and to further analyze the interaction and inhibitory mechanisms of two main phenolics (caffeic acid and catechin). Results showed that the free, esterified, and insoluble-bound phenolic fractions from the non- and UHP-treated fruits demonstrated good inhibitory effects towards two enzymes. The insoluble-bound phenolic fraction, regardless of UHP treatment, presented the strongest inhibitory capacities, and UHP treatment significantly upgraded the inhibitory effects of these phenolic fractions (lipase IC50 : 78.01 vs. 72.50 μg/mL; α-glucosidase IC50 : 76.42 vs. 64.51 μg/mL). Catechin and caffeic acid, main phenolic compounds detected in all phenolic fractions of the fruits, showed similar efficiencies on inhibiting the two enzymes, which were consistent with the findings observed by molecular docking analysis. Moreover, these two phenolic compounds exhibited a synergy effect on inhibiting pancreatic lipase and α-glucosidase at a relatively high combination concentration with the ratio of 1 : 1. Therefore, the present work may be helpful for further application of palm fruits as food supplements or nutraceuticals to control energy intake to improving some chronic metabolic diseases.